Analysis of development trends of standard of living for medium-sized cities in Poland - Cheba, Katarzyna (Analiza tendencji rozwojowych poziomu życia ludności miast średniej wielkości w Polsce, 2011)
The standard of living and living conditions of the population of Poland are spatially highly diversified. The work attempts to conduct the analysis of spatial differentiation of the standard of living of residents in a dynamic model in the years 2002-2008, on the example of medium-sized cities (50-150 thousand inhabitants). 36 cities were selected for the study. In the first step, 19 variables from the set of 45 diagnostic features were selected to the final set of variables. The work presents the study conducted in the dynamic model in addition to the analysis of changes in the groups of cities with a similar standard of living
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s, 137-146
Keywords: poziom życia; warunki życia ludności; living standard; people's living conditions